PENGARUH PENGAWASAN FASILITAS OLEH TERMINAL SERVICE OFFICER (TSO) TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Syifa Fauziah; Julius Trian (Jurnal Manajemen Dirgantara, 2024)
Passenger satisfaction is a condition that passengers feel after experiencing a performance of the service and comparing the services that passengers want according to and can be fulfilled through these services. terminal service officer (TSO) is a key aspect in smooth operations because it has the task of supervising facilities related to passenger services. This research uses quantitative methods with data collection techniques using questionnaires. The results in this study indicate that there is an influence between the supervision variable on the passenger satisfaction variable which is indicated by a Sig value of 0.000 in the T-test. The magnitude of the influence of supervision on passenger satisfaction is indicated by the coefficient of determination from domestic passengers amounting to 65.6% and international passengers amounting to 42.9%. Both having an average that is categorized as high or very high means that the supervision variable affects the passenger satisfaction variable in the descriptive test.